Investigation of Water-based and Solvent-based Polymer Binders on the Fire Protection Performance and Mechanical Properties of Intumescent Coating - Lee, Jin Sheng (2019)
The aim of this research project was to investigate and evaluate the effects of solvent-based and water-based polymer binders on the fire protection performance and mechanical properties of intumescent coatings on steel structural. In the event of fire, intumescent coating serve as a passive fire protections which will break down into vast, multi-cellular char layers that able reduce the spread of flame and penetrating of heat, to avoid failure of building components. Polymer binders were not efficient to provide excellent mechanical and fire retardant properties. Thus, optimization of intumescent formulation is important to form an effective char layer with high durability and uniform foam structure to protect the substrate. In this research project, formulation of intumescent coatings with different combinations of polymer binders and flame retardant fillers were synthesized. Influence of polymer binders and flame retardant fillers on the fire protection performance and mechanical properties of intumescent coatings were investigated through Bunsen burner test, furnace test, char layer strength test, static immersion test, adhesion strength test, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA), corrosion test and freeze-thaw cycle test. Two polymer binders (vinyl acetate and acrylic resin) were mixed with three flame retardant additives, namely ammonium polyphosphate II (APP), pentaerythritol (PER) and melamine (MEL), in the ratio of 2:1:1 and various flame-retardant fillers to synthesis the intumescent fire protective coatings. This research project found that incorporation of solvent-based polymer binders into intumescent coatings contributed better fire protection performance, water resistance, corrosion resistance and weather resistance, whereas incorporation of water-based polymer binders into intumescent coatings contributed better adhesion strength. Besides, it was also found that formulation 3 (W3 and S3) with appropriate combinations of flame retardant fillers (3.33 wt.% titanium oxide/ 3.33 wt.% magnesium hydroxide/ 3.33 wt.% expandable graphite) in the coating had contributed to positive fire protection performance and mechanical properties. Addition of water-based polymer binder into the formulation demonstrated acceptable range of fire protection performance and mechanical properties. This coating formulation had the ability to protect human lives and asset in the event of a fire by serving as life-saving coating.